Analysis Of Application In Intermediate Check And Maximum Maintenance Expenditure Limit Methods As Performance Monitoring Tools Of Baby Incubator - Ernia Susana; Reynata Maysi Novelita (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Baby incubators make the percentage of babies born safe and the ability to survive from hypothermia in premature babies is higher. Equipment maintenance is needed so that the tool is always ready to use and safe for patients. The instability of the baby incubator's technical performance can occur because of the useful life of equiments. In addition, its can affect the maintenance costs incurred. This study aims to analyze the application of the intermediate check method and the calculation of the MMEL method for baby incubators with the main criteria is the useful life of equipments. The life expectancy of baby incubator is 10 (ten) years. The results showed that the useful life of baby incubator did not reduce the stability of the average temperature and the cost of MMEL. The results of intermediate check measurements on baby incubators A, B and C respectively showed an estimated bias of ± 0.41 ºC, ± 0.36 ºC and ± 0.19 ºC.